Sleep habits and starting time to school in Brazilian children Hábitos de sono e período escolar em crianças brasileiras - Tatiana A. Silva; Luciane B.C. Carvalho; Luciana Silva; Marilaine Medeiros; Vivian B. Natale; Joao E.C. Carvalho; Lucila B.F. Prado; Gilmar F. Prado (Arquivos de Neuro-Psiquiatria)
OBJECTIVE: This study investigated the sleep habits in Brazilian children according to age, gender and starting time to school. METHOD: We investigated 2,482 scholars aged 7 to 10 years. We compared sleep habits, gender, and starting time to school (morning and afternoon). RESULTS: Sixty-one per cent of the children presented sleep rituals before sleep. Milk drinking before sleep was more frequent among seven years old children. We found a progressive reduction with age in keeping the lights on. Girls used to leave an object to bed more than boys did. Children that studied in the morning presented reduced total sleep time, sleep earlier, and nap more frequently than children that studied in the afternoon. CONCLUSION: Starting time to school deeply influences sleep habits in Brazilian children from São Paulo City, in whom bed-time rituals are highly prevalent. OBJETIVOS: Estudar os hábitos de sono nas crianças brasileiras de acordo com a idade, sexo e período escolar. MÉTODO: Estudamos 2.482 crianças em idade escolar de 7 a 10 anos. Comparamos hábitos de sono, sexo e período escolar (matutino e vespertino). RESULTADOS: 61% das crianças apresentaram rituais de sono antes de dormir. Beber leite antes de dormir foi mais freqüente entre as crianças de 7 anos de idade. Encontramos redução progressiva com a idade em se manter a luz acesa. Meninas possuíam mais objetos para dormir que os meninos. As crianças que estudavam no período matutino apresentaram redução do tempo total de sono, tinham sono mais cedo e os cochilos eram mais freqüentes do que as crianças que estudavam no período vespertino. CONCLUSÃO: O horário escolar tem muita influência nos hábitos de sono das crianças brasileiras da cidade de São Paulo, os rituais de sono sendo muito prevalentes.